Development of a PCR assay for the identification of the parasite Dawestrema (Trematoda: Monogenea) in Arapaima gigas fish - Serrano-Martínez, Enrique (2016)
Studies in the Amazonian species Arapaima gigas («paiche») have demonstrated the presence of Dawestrema cycloancistrium monogenean parasite in high parasite loads, mainly in stages between 180 and 365 days of age. D. cycloancistrium adheres to the gills causing a decrease in the degree of oxygenation and stress on the fish predisponing to disease presentation. This study aimed to develop a molecular diagnostic technique for D. cycloancistrium in order to aply it in the management of the fish biodiversity. For this purpose, 200 specimens of D. cycloancistrium were collected, DNA was extracted and quantified, primers were designed and a PCR was developed. The amplification of a sequence of 236 bp of the Dawestrema monogenean was obtained.